The new American exceptionalism - Pease, Donald E. (Minneapolis University Of Minnesota Press, 2009)
For a half century following the end of World War II, the seemingly permanent cold war provided the United States with an organizing logic that governed nearly every aspect of American society and culture, giving rise to an unwavering belief in the nation's exceptionalism in global affairs and world history. After the collapse of the Soviet Union, this cold war paradigm was replaced by a series of new ideological narratives that ultimately resulted in the establishment of another potentially endless war: the global war on terror.In The New American Exceptionalism, pioneering scholar Donald E. Pease traces the evolution of these state fantasies and shows how they have shaped U.S. national identity since the end of the cold war, uncovering the ideological and cultural work required to convince Americans to surrender their civil liberties in exchange for the illusion of security. His argument follows the chronology of the transitions between paradigms from the inauguration of the New World Order under George H. W. Bush to the homeland security state that George W. Bush's administration installed in the wake of 9/11. Providing clear and convincing arguments about how the concept of American exceptionalism was reformulated and redeployed in this era, Pease examines a wide range of cultural works and political spectacles, including the exorcism of the Vietnam syndrome through victory in the Persian Gulf War and the creation of Islamic extremism as an official state enemy.At the same time, Pease notes that state fantasies cannot altogether conceal the inconsistencies they mask, showing how such events as the revelations of prisoner abuse at Abu Ghraib and the exposure of government incompetence after Hurricane Katrina opened fissures in the myth of exceptionalism, allowing Barack Obama to challenge the homeland security paradigm with an alternative state fantasy that privileges fairness, inclusion, and justice.
Keywords: National characteristics, American